The Biological Functions and Clinical Applications of Integrins in Cancers - Su, Chao-yue; Li, Jing-quan; Zhang, Ling-ling; Wang, Hui; Wang, Feng-hua; Tao, Yi-wen; Wang, Yu-qing; Guo, Qiao-ru; Li, Jia-jun; Liu, Yun; Yan, Yan-yan; Zhang, Jian-ye (Frontiers in Pharmacology, 2020)
Integrins are the adhesion molecules and receptors of extracellular matrix (ECM). They mediate the interactions between cells-cells and cells-ECM. The crosstalk between cancer cells and their microenvironment triggers a variety of critical signaling cues and promotes the malignant phenotype of cancer. As a type of transmembrane protein, integrin-mediated cell adhesion is essential in regulating various biological functions of cancer cells. Recent evidence has shown that integrins present on tumor cells or tumor-associated stromal cells are involved in ECM remodeling, and as mechanotransducers sensing changes in the biophysical properties of the ECM, which contribute to cancer metastasis, stemness and drug resistance. In this review, we outline the mechanism of integrin-mediated effects on biological changes of cancers and highlight the current status of clinical treatments by targeting integrins.